Accounting Training to Support Transparent and Accountable Village Fund Reporting in Sibetan Village, Karangasem Bali - SAPUTRA, Komang Adi Kurniawan; LAKSMI, Putu Ayu Sita; SURIANI, Nyoman; EKAJAYANTI, L.G.P Sri (PT Batara Swastika Harati, 2024)
This community service aims to socialize regulations and mechanisms for managing village fund allocations for community welfare. The governance of village funds plays a vital role in transforming villages into independent and sustainable communities. Good management of village funds will encourage the community to enhance the economy and explore the Village's potential. Village officials also receive significant attention in the regulations governing village fund management. The speakers explain the village fund allocation management flow and its purposes in this community service. The desired expectation is that officials refrain from engaging in activities related to financial management violations, practice sound financial management, create innovations and creativity using village funds, and establish new sources of income to increase the Village's original revenue.